INFRASTRUCTURE FROM CYBER AND PHYSICAL THREATS - Durgesh Kumar Thakur (International Journal of Multidisciplinary Research and Studies, 2021)
Cyber-physical systems, often known as CPS for short, are intelligent systems that consist of constructed networks of both physical and computational components that interact with one another. Being resilient is one of the primary criteria for a CPS, so make sure yours is (NIS, 2017). The next version of the CPS has to be resistant to correlated threats, which are attacks in which more than one attacker operates on an entity. Correlated risks arise in situations in which simple perimeter safeguards are insufficient